A modified plastic and its preparation method and application
By adding modified fibers, modified silica and flame retardant to the polycarbonate, and using ball milling and blending processes, modified plastics with excellent mechanical, flame retardant and antibacterial properties are prepared, which solves the problem of insufficient plastic performance in the prior art.
Patent Information
- Application Number
- CN202411209343.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-08-30
AI Technical Summary
In the prior art, the flame retardant properties, antibacterial properties and mechanical properties of plastics are poor, making it difficult to meet the higher requirements for material performance in high-end fields.
Modified plastics with excellent properties were prepared by adding modified carbon fibers, modified silica, quaternary fluorohexylphosphine salt components, quaternary fluorodecylphosphine salt components and coated flame retardant components to the polycarbonate, and processing them by ball milling and blending.
It significantly improves the mechanical properties, thermal stability, weather resistance and corrosion resistance of modified plastics, and at the same time enhances its flame retardant and antibacterial properties, and is suitable for packaging, electronics and electrical appliances and automotive industries.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of plastic preparation methods, and in particular to a modified plastic and a preparation method and application thereof. Background Art
[0002] In the field of plastics industry, traditional plastics have been widely used in packaging, electronic appliances, automobile industry and other fields due to their advantages such as low cost and good processing performance. However, with the advancement of science and technology and the continuous development of the market, the limitations of traditional plastics in performance have gradually emerged, such as insufficient strength, poor heat resistance, poor flame retardancy and easy mildew, which make it difficult to meet the higher requirements of material performance in high-end fields. Therefore, modified plastics, as a new type of material modified on the basis of traditional plastics by physical or chemical means, have gradually become a research hotspot in the plastics industry.
[0003] Modified plastics can significantly improve the mechanical properties, heat resistance, chemical corrosion resistance, and special optical, electrical, and thermal properties of plastics by adding various functional additives or modifiers to the plastic matrix, such as reinforcing materials including glass fiber and carbon fiber, toughening agents, flame retardants, antibacterial agents, etc. These excellent properties make modified plastics have broad application prospects in the fields of packaging materials, electronic and electrical materials, and automotive industry materials. Summary of the invention
[0004] Technical issues solved
[0005] In view of the above-mentioned shortcomings of the prior art, the present invention provides a modified plastic and a preparation method and application thereof, which can effectively solve the problems of poor flame retardancy, antibacterial properties and mechanical properties of the plastics in the prior art.
[0006] Technical Solution
[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0008] A modified plastic, wherein the raw materials of the modified plastic include the following components by weight: 500 parts of polycarbonate, 12-15 parts of modified polyacrylate emulsion, 5-8 parts of composite antibacterial component, 6-10 parts of coated flame retardant component and 3-4 parts of silane coupling agent KH-560;
[0009] The modified polyacrylate emulsion is prepared by modifying the polyacrylate emulsion with modified carbon fiber and modified silicon dioxide;
[0010] The composite antibacterial component is prepared by mixing a quaternary fluorohexylphosphonium salt component and a quaternary fluorodecylphosphonium salt component in an equal weight ratio;
[0011] The coated flame retardant component is prepared by coating ammonium polyphosphate with chitosan and sodium phytate.
[0012] Furthermore, the preparation method of the modified carbon fiber is:
[0013] S2.1, ethanol and acetone are mixed in an equal volume ratio to prepare an impregnation solution, the carbon fiber is immersed in the impregnation solution for 24 hours, the filtrate is filtered to remove the filtrate, and then dried in an oven at 55° C. for 2-3 hours, and the obtained carbon fiber is recorded as the pretreated carbon fiber;
[0014] S2.2. Weigh 2g of dopamine hydrochloride and dissolve it in 1L of 0.01mol / L Tris solution to prepare a modified solution. Then, immerse the pretreated carbon fiber in the modified solution for 15-18h. After filtering out the filtrate, dry it in an oven at 48°C for 2-3h to obtain the modified carbon fiber.
[0015] Furthermore, the preparation method of the modified silica is: weigh 20g of nano-silica powder and pour it into 200mL of isopropanol, then add 3-5g of dodecyltrimethylammonium chloride, 1-2g of hexadecyldimethylbenzylammonium chloride, 3-4g of didecyldimethylammonium chloride and 2-3g of tetradecyltrimethylammonium bromide, ultrasonically disperse at a frequency of 28kHz for 10min, then add 2-3g of silane coupling agent KH-570, stir at a speed of 800r / min for 20min, and then place in an oven at 80°C to dry to constant weight, and the obtained is modified silica.
[0016] Furthermore, the preparation method of the modified polyacrylate emulsion is: weigh 1-2g of modified carbon fiber, 2-3g of modified silica and 1g of silane coupling agent KH-570, pour them into 20mL of polyacrylate emulsion, stir at a speed of 500r / min for 30min, and the obtained polyacrylate emulsion is obtained.
[0017] Furthermore, the preparation method of the quaternary fluorohexyl phosphonium salt component is as follows: 5 g of triphenylphosphine and 9 g of perfluorohexyl iodide are weighed and dissolved in acetonitrile solvent, stirred at a speed of 200 r / min for 48 hours in a water bath at 75°C, then the acetonitrile solvent is removed by rotary evaporation at a rotary evaporation temperature of 40°C, the obtained product is washed with ether 3 times, and finally placed in a vacuum drying oven at 35°C and dried for 8 hours, and the obtained product is the quaternary fluorohexyl phosphonium salt component.
[0018] Furthermore, the preparation method of the quaternary fluorodecyl phosphonium salt component is as follows: 5 g of triphenylphosphine and 9 g of perfluorodecyl iodide are weighed and dissolved in acetonitrile solvent, stirred at a speed of 200 r / min for 48 hours in a water bath at 75°C, then the acetonitrile solvent is removed by rotary evaporation at a rotary evaporation temperature of 40°C, the obtained product is washed with ether 3 times, and finally placed in a vacuum drying oven at 35°C and dried for 8 hours, and the obtained product is the quaternary fluorodecyl phosphonium salt component.
[0019] Furthermore, the preparation method of the coated flame retardant component is as follows: weigh 5-6g of chitosan and dissolve it in 250mL of 1% acetic acid solution, stir it at a speed of 300r / min in a water bath at 25°C until it is dissolved, then heat it to 60°C and add 8-10g of ammonium polyphosphate, then stir it at the original speed for 1h, add 10g of 10% sodium phytate solution, continue the reaction for 1h, and then obtain the product component by suction filtration, wash the product component 3 times with deionized water and place it in an oven at 55°C to dry to constant weight, and the obtained product is the coated flame retardant component.
[0020] A method for preparing a modified plastic, the preparation method comprising:
[0021] S1, weigh the above-mentioned composite antibacterial component and coated flame retardant component in parts by weight, pour them into a ball mill for ball milling, add the above-mentioned silane coupling agent KH-560 in parts by weight after ball milling for 10 minutes, and continue ball milling for 10 minutes, the result is recorded as the first component;
[0022] S2. Pour the first component in S1 and the above-mentioned weight parts of polycarbonate and modified polyacrylate emulsion into a torque rheometer, blend them at a temperature of 230-250°C for 8-10 minutes, then pour them into a flat vulcanizer, and then at a pressure of 10-12MPa and a temperature of 180-200°C for 2-5 minutes to obtain a modified plastic.
[0023] Furthermore, in S1, the material-ball ratio of the ball mill is 1:2, and the rotation speed of the ball mill is 300 r / min.
[0024] The invention discloses an application of modified plastics, which includes packaging materials, electronic and electrical materials, and automotive industry materials.
[0025] Beneficial Effects
[0026] The present invention provides a modified plastic and a preparation method and application thereof. Compared with the prior art, the present invention has the following beneficial effects:
[0027] 1. The present invention adds carbon fiber modified by polydopamine coating and nano-silica modified by silane coupling agent into polyacrylate emulsion, and then blends the carbon fiber with polycarbonate to prepare modified plastic, which can improve the mechanical properties, thermal stability, weather resistance and corrosion resistance of the modified plastic; since the carbon fiber itself has the properties of high strength and high modulus, after being coated and modified by polydopamine, the interfacial bonding force between the carbon fiber and the polymer matrix is enhanced, and the excellent mechanical properties of the carbon fiber can be effectively transferred to the polymer matrix, thereby improving the overall mechanical properties of the modified plastic, such as tensile strength, flexural strength and modulus; secondly, after the nano-silica particles are modified by silane coupling agent, they can be uniformly Evenly dispersed in the polyacrylate emulsion, reducing agglomeration, so as to more effectively play the reinforcing role of nanoparticles, the addition of nano-silica can further improve the hardness and rigidity of the modified plastic, while improving the impact resistance of the modified plastic, it can also improve the corrosion resistance of the modified plastic, and resist the erosion of acid, alkali and other chemical substances; finally, the modified carbon fiber and modified silica are first dispersed in the polyacrylate emulsion, and then blended with polycarbonate. With the help of the good fluidity of the polyacrylate emulsion itself, the modified carbon fiber and modified silica are more evenly dispersed in the polycarbonate and blended with it, and the prepared modified plastic can also have excellent overall thermal stability.
[0028] 2. The present invention adds a quaternary fluorohexyl phosphonium salt component, a quaternary fluorodecyl phosphonium salt component and ammonium polyphosphate coated with chitosan and sodium phytate into polycarbonate for blending, which can improve the flame retardant properties, processing properties, physical and mechanical properties and antibacterial properties of the modified plastic; ammonium polyphosphate itself has good flame retardant properties, and its flame retardant efficiency can be further improved by coating with chitosan and sodium phytate, and the addition of chitosan and sodium phytate can improve the dispersibility of ammonium polyphosphate in polycarbonate, and chitosan has a carbonizing effect, which can form a protective layer during the combustion process to isolate oxygen and heat, thereby enhancing the flame retardant effect; secondly, quaternary fluorohexyl phosphonium salt and quaternary fluorodecyl phosphonium salt are blended with polycarbonate, and can interact with the polycarbonate molecular chain to form a more stable network structure, thereby improving the thermal stability, weather resistance and mechanical properties of the material. Since quaternary fluorohexyl phosphonium salt and quaternary fluorodecyl phosphonium salt have stable antibacterial properties, blending them with polycarbonate can improve the antibacterial properties of the modified plastic.
[0029] 3. The modified plastic prepared by the present invention has excellent performance, can have good market application prospects, and has extremely good application value in the fields of packaging raw materials, electronic and electrical materials, and automotive industrial materials. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] The present invention will be further described below in conjunction with the embodiments.
[0032] Example 1
[0033] A modified plastic of this embodiment, the raw materials of the modified plastic include the following components by weight: 500 parts of polycarbonate, 12 parts of modified polyacrylate emulsion, 5 parts of composite antibacterial component, 6 parts of coated flame retardant component and 3 parts of silane coupling agent KH-560;
[0034] The modified polyacrylate emulsion is prepared by modifying the polyacrylate emulsion with modified carbon fiber and modified silicon dioxide;
[0035] Wherein, the preparation method of modified carbon fiber is:
[0036] S2.1, ethanol and acetone are mixed in an equal volume ratio to prepare an impregnation solution, the carbon fiber is immersed in the impregnation solution for 24 hours, the filtrate is filtered to remove the filtrate, and then dried in an oven at 55° C. for 2 hours, and the obtained carbon fiber is recorded as the pretreated carbon fiber;
[0037] S2.2. Weigh 2 g of dopamine hydrochloride and dissolve it in 1 L of 0.01 mol / L Tris solution to prepare a modified solution. Then, immerse the pretreated carbon fiber in the modified solution for 15 h. After filtering out the filtrate, dry it in an oven at 48°C for 2 h. The result is the modified carbon fiber.
[0038] The preparation method of modified silica is as follows: weigh 20g of nano-silica powder and pour it into 200mL of isopropanol, then add 3g of dodecyltrimethylammonium chloride, 1g of hexadecyldimethylbenzylammonium chloride, 3g of didecyldimethylammonium chloride and 2g of tetradecyltrimethylammonium bromide, ultrasonically disperse at a frequency of 28kHz for 10min, then add 2g of silane coupling agent KH-570, stir at a speed of 800r / min for 20min, and then place in an oven at 80°C and dry to constant weight, and the result is modified silica.
[0039] The preparation method of the modified polyacrylate emulsion is as follows: weigh 1g of modified carbon fiber, 2g of modified silica and 1g of silane coupling agent KH-570, pour them into 20mL of polyacrylate emulsion, stir at a speed of 500r / min for 30min, and the obtained polyacrylate emulsion is obtained.
[0040] The composite antibacterial component is prepared by mixing a quaternary fluorohexylphosphonium salt component and a quaternary fluorodecylphosphonium salt component in an equal weight ratio;
[0041] Among them, the preparation method of the quaternary fluorohexyl phosphonium salt component is: weigh 5g of triphenylphosphine and 9g of perfluorohexyl iodide and dissolve them in acetonitrile solvent, stir at a speed of 200r / min for 48h in a water bath condition of 75°C, then remove the acetonitrile solvent by rotary evaporation at a rotary evaporation temperature of 40°C, wash the obtained product with ether 3 times, and finally place it in a vacuum drying oven at 35°C and dry it for 8h, and the obtained product is the quaternary fluorohexyl phosphonium salt component.
[0042] The preparation method of the quaternary fluorodecyl phosphonium salt component is as follows: 5 g of triphenylphosphine and 9 g of perfluorodecyl iodide are weighed and dissolved in an acetonitrile solvent, stirred at a speed of 200 r / min for 48 hours in a water bath at 75°C, then the acetonitrile solvent is removed by rotary evaporation at a rotary evaporation temperature of 40°C, the obtained product is washed three times with ether, and finally dried in a vacuum drying oven at 35°C for 8 hours, and the obtained product is the quaternary fluorodecyl phosphonium salt component.
[0043] The coated flame retardant component is prepared by coating ammonium polyphosphate with chitosan and sodium phytate;
[0044] Among them, the preparation method of the coated flame retardant component is: weigh 5g of chitosan and dissolve it in 250mL of 1% acetic acid solution, stir it at a speed of 300r / min in a water bath at 25°C until it is dissolved, then heat it to 60°C and add 8g of ammonium polyphosphate, then stir it at the original speed for 1h, then add 10g of 10% sodium phytate solution, continue to react for 1h, and then obtain the product component by suction filtration, wash the product component with deionized water 3 times and place it in an oven at 55°C to dry to constant weight, and the obtained product is the coated flame retardant component.
[0045] A method for preparing a modified plastic, the preparation method comprising:
[0046] S1, weigh the above-mentioned composite antibacterial component and coated flame retardant component in parts by weight, pour them into a ball mill for ball milling, the material-ball ratio of ball milling is 1:2, the speed of ball milling is 300r / min, after ball milling for 10min, add the above-mentioned weight portion of silane coupling agent KH-560 and continue ball milling for 10min, the obtained result is recorded as the first component;
[0047] S2. Pour the first component in S1 and the above-mentioned weight portions of polycarbonate and modified polyacrylate emulsion into a torque rheometer, blend them at a temperature of 230°C for 80 minutes, and then pour them into a flat vulcanizer, and then at a pressure of 10 MPa and a temperature of 180°C for 2 minutes to obtain a modified plastic.
[0048] The invention discloses an application of modified plastics, including packaging materials, electronic and electrical materials, and automotive industry materials.
[0049] Example 2
[0050] A modified plastic of this embodiment, the raw materials of the modified plastic include the following components by weight: 500 parts of polycarbonate, 15 parts of modified polyacrylate emulsion, 8 parts of composite antibacterial component, 10 parts of coated flame retardant component and 4 parts of silane coupling agent KH-560;
[0051] The modified polyacrylate emulsion is prepared by modifying the polyacrylate emulsion with modified carbon fiber and modified silicon dioxide;
[0052] Wherein, the preparation method of modified carbon fiber is:
[0053] S2.1, ethanol and acetone are mixed in an equal volume ratio to prepare an impregnation solution, the carbon fiber is immersed in the impregnation solution for 24 hours, the filtrate is filtered to remove the filtrate, and then dried in an oven at 55° C. for 3 hours, and the obtained carbon fiber is recorded as the pretreated carbon fiber;
[0054] S2.2. Weigh 2g of dopamine hydrochloride and dissolve it in 1L of 0.01mol / L Tris solution to prepare a modified solution. Then, immerse the pretreated carbon fiber in the modified solution for 18h. After filtering out the filtrate, dry it in an oven at 48°C for 3h to obtain the modified carbon fiber.
[0055] The preparation method of modified silica is as follows: weigh 20g of nano-silica powder and pour it into 200mL of isopropanol, then add 5g of dodecyltrimethylammonium chloride, 2g of hexadecyldimethylbenzylammonium chloride, 4g of didecyldimethylammonium chloride and 3g of tetradecyltrimethylammonium bromide, ultrasonically disperse at a frequency of 28kHz for 10min, then add 3g of silane coupling agent KH-570, stir at a speed of 800r / min for 20min, and then place in an oven at 80°C and dry to constant weight, and the result is modified silica.
[0056] The preparation method of the modified polyacrylate emulsion is as follows: weigh 2g of modified carbon fiber, 3g of modified silica and 1g of silane coupling agent KH-570, pour them into 20mL of polyacrylate emulsion, stir at a speed of 500r / min for 30min, and the obtained product is the modified polyacrylate emulsion.
[0057] The composite antibacterial component is prepared by mixing a quaternary fluorohexylphosphonium salt component and a quaternary fluorodecylphosphonium salt component in an equal weight ratio;
[0058] Among them, the preparation method of the quaternary fluorohexyl phosphonium salt component is: weigh 5g of triphenylphosphine and 9g of perfluorohexyl iodide and dissolve them in acetonitrile solvent, stir at a speed of 200r / min for 48h in a water bath condition of 75°C, then remove the acetonitrile solvent by rotary evaporation at a rotary evaporation temperature of 40°C, wash the obtained product with ether 3 times, and finally place it in a vacuum drying oven at 35°C and dry it for 8h, and the obtained product is the quaternary fluorohexyl phosphonium salt component.
[0059] The preparation method of the quaternary fluorodecyl phosphonium salt component is as follows: 5 g of triphenylphosphine and 9 g of perfluorodecyl iodide are weighed and dissolved in an acetonitrile solvent, stirred at a speed of 200 r / min for 48 hours in a water bath at 75°C, then the acetonitrile solvent is removed by rotary evaporation at a rotary evaporation temperature of 40°C, the obtained product is washed three times with ether, and finally dried in a vacuum drying oven at 35°C for 8 hours, and the obtained product is the quaternary fluorodecyl phosphonium salt component.
[0060] The coated flame retardant component is prepared by coating ammonium polyphosphate with chitosan and sodium phytate;
[0061] Among them, the preparation method of the coated flame retardant component is: weigh 6g of chitosan and dissolve it in 250mL of 1% acetic acid solution, stir it at a speed of 300r / min in a water bath at 25°C until it is dissolved, then heat it to 60°C and add 10g of ammonium polyphosphate, then stir it at the original speed for 1h, then add 10g of 10% sodium phytate solution, continue the reaction for 1h, and then obtain the product component by suction filtration, wash the product component three times with deionized water and place it in an oven at 55°C to dry to constant weight, and the result is the coated flame retardant component.
[0062] A method for preparing a modified plastic, the preparation method comprising:
[0063] S1, weigh the above-mentioned composite antibacterial component and coated flame retardant component in parts by weight, pour them into a ball mill for ball milling, the material-ball ratio of ball milling is 1:2, the speed of ball milling is 300r / min, after ball milling for 10min, add the above-mentioned weight portion of silane coupling agent KH-560 and continue ball milling for 10min, the obtained result is recorded as the first component;
[0064] S2. Pour the first component in S1 and the above-mentioned weight parts of polycarbonate and modified polyacrylate emulsion into a torque rheometer, blend them at a temperature of 250°C for 10 minutes, and then pour them into a flat vulcanizer, and then keep them at a pressure of 12 MPa and a temperature of 200°C for 5 minutes to obtain a modified plastic.
[0065] The invention discloses an application of modified plastics, including packaging materials, electronic and electrical materials, and automotive industry materials.
[0066] Example 3
[0067] A modified plastic of this embodiment, the raw materials of the modified plastic include the following components by weight: 500 parts of polycarbonate, 14 parts of modified polyacrylate emulsion, 7 parts of composite antibacterial component, 8 parts of coated flame retardant component and 4 parts of silane coupling agent KH-560;
[0068] The modified polyacrylate emulsion is prepared by modifying the polyacrylate emulsion with modified carbon fiber and modified silicon dioxide;
[0069] Wherein, the preparation method of modified carbon fiber is:
[0070] S2.1, ethanol and acetone are mixed in an equal volume ratio to prepare an impregnation solution, the carbon fiber is immersed in the impregnation solution for 24 hours, the filtrate is filtered to remove the filtrate, and then dried in an oven at 55° C. for 3 hours, and the obtained carbon fiber is recorded as the pretreated carbon fiber;
[0071] S2.2. Weigh 2g of dopamine hydrochloride and dissolve it in 1L of 0.01mol / L Tris solution to prepare a modified solution. Then, immerse the pretreated carbon fiber in the modified solution for 16h. After filtering out the filtrate, dry it in an oven at 48°C for 3h to obtain the modified carbon fiber.
[0072] The preparation method of modified silica is as follows: weigh 20g of nano-silica powder and pour it into 200mL of isopropanol, then add 4g of dodecyltrimethylammonium chloride, 2g of hexadecyldimethylbenzylammonium chloride, 4g of didecyldimethylammonium chloride and 2g of tetradecyltrimethylammonium bromide, ultrasonically disperse at a frequency of 28kHz for 10min, then add 3g of silane coupling agent KH-570, stir at a speed of 800r / min for 20min, and then place in an oven at 80°C and dry to constant weight, and the result is modified silica.
[0073] The preparation method of the modified polyacrylate emulsion is as follows: weigh 2g of modified carbon fiber, 2g of modified silica and 1g of silane coupling agent KH-570, pour them into 20mL of polyacrylate emulsion, stir at a speed of 500r / min for 30min, and the obtained product is the modified polyacrylate emulsion.
[0074] The composite antibacterial component is prepared by mixing a quaternary fluorohexylphosphonium salt component and a quaternary fluorodecylphosphonium salt component in an equal weight ratio;
[0075] Among them, the preparation method of the quaternary fluorohexyl phosphonium salt component is: weigh 5g of triphenylphosphine and 9g of perfluorohexyl iodide and dissolve them in acetonitrile solvent, stir at a speed of 200r / min for 48h in a water bath condition of 75°C, then remove the acetonitrile solvent by rotary evaporation at a rotary evaporation temperature of 40°C, wash the obtained product with ether 3 times, and finally place it in a vacuum drying oven at 35°C and dry it for 8h, and the obtained product is the quaternary fluorohexyl phosphonium salt component.
[0076] The preparation method of the quaternary fluorodecyl phosphonium salt component is as follows: 5 g of triphenylphosphine and 9 g of perfluorodecyl iodide are weighed and dissolved in an acetonitrile solvent, stirred at a speed of 200 r / min for 48 hours in a water bath at 75°C, then the acetonitrile solvent is removed by rotary evaporation at a rotary evaporation temperature of 40°C, the obtained product is washed three times with ether, and finally dried in a vacuum drying oven at 35°C for 8 hours, and the obtained product is the quaternary fluorodecyl phosphonium salt component.
[0077] The coated flame retardant component is prepared by coating ammonium polyphosphate with chitosan and sodium phytate;
[0078] Among them, the preparation method of the coated flame retardant component is: weigh 6g of chitosan and dissolve it in 250mL of 1% acetic acid solution, stir it at a speed of 300r / min in a water bath at 25°C until it is dissolved, then heat it to 60°C and add 9g of ammonium polyphosphate, then stir it at the original speed for 1h, then add 10g of 10% sodium phytate solution, continue the reaction for 1h, and then obtain the product component by suction filtration, wash the product component with deionized water 3 times and place it in an oven at 55°C to dry to constant weight, and the obtained product is the coated flame retardant component.
[0079] A method for preparing a modified plastic, the preparation method comprising:
[0080] S1, weigh the above-mentioned composite antibacterial component and coated flame retardant component in parts by weight, pour them into a ball mill for ball milling, the material-ball ratio of ball milling is 1:2, the speed of ball milling is 300r / min, after ball milling for 10min, add the above-mentioned weight portion of silane coupling agent KH-560 and continue ball milling for 10min, the obtained result is recorded as the first component;
[0081] S2. Pour the first component in S1 and the above-mentioned weight parts of polycarbonate and modified polyacrylate emulsion into a torque rheometer, blend them at a temperature of 240°C for 9 minutes, and then pour them into a flat vulcanizer, and then at a pressure of 11 MPa and a temperature of 190°C for 4 minutes to obtain a modified plastic.
[0082] The invention discloses an application of modified plastics, including packaging materials, electronic and electrical materials, and automotive industry materials.
[0083] Comparative Example 1
[0084] The modified plastic and the preparation method thereof provided in this comparative example are substantially the same as those in Example 1, with the main difference being that in this comparative example 1, the modified polyacrylate emulsion in Example 1 is replaced with a commercially available polyacrylate emulsion of model number 9003-01-4.
[0085] Comparative Example 2
[0086] The modified plastic and the preparation method thereof provided in this comparative example are substantially the same as those in Example 1, with the main difference being that in this comparative example 2, the composite antibacterial component in Example 1 is replaced by the quaternary fluorohexylphosphonate component in Example 1.
[0087] Comparative Example 3
[0088] The modified plastic and the preparation method thereof provided in this comparative example are substantially the same as those in Example 1, with the main difference being that in this comparative example 3, the coated flame retardant component in Example 1 is replaced with ammonium polyphosphate of model APP1000 available on the market.
[0089] Performance Testing
[0090] The modified plastics in Examples 1-3 and Comparative Examples 1-3 are marked as Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2 and Comparative Example 3, respectively. Then, the performance of Examples 1-3 and Comparative Examples 1-3 is tested. The specific test items and test methods are as follows:
[0091] 1. According to the test standard of ASTM D2863, the limiting oxygen index (LOI) of Examples 1-3 and Comparative Examples 1-3 was tested using an oxygen index meter, and the obtained data were recorded in the following table;
[0092] 2. The tensile strength and elongation at break of Examples 1-3 and Comparative Examples 1-3 were tested according to the standard of ASTM D638-22, with a tensile rate of 100 mm / min. The obtained data are recorded in the following table;
[0093] 3. The bending strength and bending modulus of Examples 1-3 and Comparative Examples 1-3 were measured according to the standard of ASTM D790-17, with a bending rate of 5 mm / min. The obtained data are recorded in the following table;
[0094] 4. Referring to the test standard of GB / T31402-2015, the plate count method was used to test the antibacterial effects of Examples 1-3 and Comparative Examples 1-3 on Escherichia coli, Staphylococcus aureus, rod-shaped bacteria and Aspergillus. Taking Escherichia coli as an example, the specific method is as follows: First, the blank glass, Examples 1-3 and Comparative Examples 1-3 were co-cultured with Escherichia coli for 24 hours. After the culture was completed, the bacterial solution was diluted 10 times. In the test, the dilution was selected as 10 5 The diluted bacterial solution was spread on agar plates and placed in a constant temperature incubator at 37°C for 24 hours. Finally, the number of colonies was recorded and the antibacterial rate was calculated according to the following formula:
[0095] Antibacterial rate = (C-C1) / C×100%
[0096] Wherein, C is the bacterial concentration of the blank glass co-culture, in CFU / mL; C1 is the bacterial concentration of the co-culture of Examples 1-3 and Comparative Examples 1-3, in CFU / mL, respectively. The obtained data are recorded in the following table.
[0097]
[0098] Table 2
[0099]
[0100] It can be seen from the data in Table 1 that the flame retardant properties and mechanical properties of the modified plastics in Examples 1-3 are significantly better than those in Comparative Examples 1-3, indicating that the addition of the enhanced polyacrylate emulsion in the preparation of the modified plastic can improve the mechanical properties of the modified plastic, and the addition of the coated flame retardant component can improve the flame retardant properties of the modified plastic. Secondly, it can be seen from the data in Table 1 that the antibacterial properties of the modified plastics in Examples 1-3 are significantly better than those in Comparative Examples 1-2, indicating that the enhanced polyacrylate emulsion and the composite antibacterial component added in the preparation of the modified plastic can enhance the antibacterial properties of the modified plastic. In summary, a modified plastic and a preparation method thereof in the present invention have excellent market application prospects.
[0101] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0102] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A modified plastic, characterized in that: The raw materials of the modified plastic include the following components by weight: 500 parts of polycarbonate, 12-15 parts of modified polyacrylate emulsion, 5-8 parts of composite antibacterial component, 6-10 parts of coated flame retardant component and 3-4 parts of silane coupling agent KH-560; The modified polyacrylate emulsion is prepared by modifying the polyacrylate emulsion with modified carbon fiber and modified silicon dioxide; The composite antibacterial component is prepared by mixing a quaternary fluorohexylphosphonium salt component and a quaternary fluorodecylphosphonium salt component in an equal weight ratio; The coated flame retardant component is prepared by coating ammonium polyphosphate with chitosan and sodium phytate; The preparation method of the modified carbon fiber is: S2.1, ethanol and acetone are mixed in an equal volume ratio to prepare an impregnation solution, the carbon fiber is immersed in the impregnation solution for 24 hours, the filtrate is filtered to remove the filtrate, and then dried in an oven at 55° C. for 2-3 hours, and the obtained carbon fiber is recorded as the pretreated carbon fiber; S2.2, weigh 2g of dopamine hydrochloride and dissolve it in 1L of Tris solution with a concentration of 0.01mol / L to prepare a modified solution, then immerse the pretreated carbon fiber in the modified solution for 15-18h, filter out the filtrate and dry it in an oven at 48°C for 2-3h, and the obtained carbon fiber is the modified carbon fiber; The preparation method of the modified silicon dioxide is as follows: 20g of nano silicon dioxide powder is weighed and poured into 200mL of isopropanol, then 3-5g of dodecyltrimethylammonium chloride, 1-2g of hexadecyldimethylbenzylammonium chloride, 3-4g of didecyldimethylammonium chloride and 2-3g of tetradecyltrimethylammonium bromide are added, and 2-3g of silane coupling agent KH-570 is added after ultrasonic dispersion at a frequency of 28kHz for 10min, and the mixture is stirred at a speed of 800r / min for 20min and then placed in an oven at 80°C and dried to constant weight, thereby obtaining the modified silicon dioxide.
2. A modified plastic according to claim 1, characterized in that: The preparation method of the modified polyacrylate emulsion is as follows: 1-2g of modified carbon fiber, 2-3g of modified silica and 1g of silane coupling agent KH-570 are weighed and poured into 20mL of polyacrylate emulsion, and stirred at a speed of 500r / min for 30min to obtain the modified polyacrylate emulsion.
3. A modified plastic according to claim 1, characterized in that: The preparation method of the quaternary fluorohexyl phosphonium salt component is as follows: 5 g of triphenylphosphine and 9 g of perfluorohexyl iodide are weighed and dissolved in an acetonitrile solvent, stirred at a speed of 200 r / min for 48 hours in a water bath at 75° C., then the acetonitrile solvent is removed by rotary evaporation at a rotary evaporation temperature of 40° C., the obtained product is washed with ether for 3 times, and finally dried in a vacuum drying oven at 35° C. for 8 hours, and the obtained product is the quaternary fluorohexyl phosphonium salt component.
4. A modified plastic according to claim 1, characterized in that: The preparation method of the quaternary fluorodecyl phosphonium salt component is as follows: 5 g of triphenylphosphine and 9 g of perfluorodecyl iodide are weighed and dissolved in an acetonitrile solvent, and stirred at a speed of 200 r / min for 48 hours in a water bath at 75° C., and then the acetonitrile solvent is removed by rotary evaporation at a rotary evaporation temperature of 40° C. The obtained product is washed with ether for 3 times, and finally placed in a vacuum drying oven at 35° C. and dried for 8 hours, and the obtained product is the quaternary fluorodecyl phosphonium salt component.
5. A modified plastic according to claim 1, characterized in that: The preparation method of the coated flame retardant component is as follows: weigh 5-6g of chitosan and dissolve it in 250mL of 1% acetic acid solution, stir at a speed of 300r / min in a water bath at 25°C until dissolved, then heat to 60°C and add 8-10g of ammonium polyphosphate, then stir at the original speed for 1h, add 10g of 10% sodium phytate solution, continue to react for 1h, and then obtain a product component by suction filtration, wash the product component with deionized water for 3 times, and place it in an oven at 55°C to dry to constant weight, and the obtained product is the coated flame retardant component.
6. A method for preparing a modified plastic according to any one of claims 1 to 5, characterized in that: The preparation method is: S1, weigh the above-mentioned composite antibacterial component and coated flame retardant component in parts by weight, pour them into a ball mill for ball milling, add the above-mentioned silane coupling agent KH-560 in parts by weight after ball milling for 10 minutes, and continue ball milling for 10 minutes, the result is recorded as the first component; S2. Pour the first component in S1 and the above-mentioned weight parts of polycarbonate and modified polyacrylate emulsion into a torque rheometer, blend them at a temperature of 230-250°C for 8-10 minutes, then pour them into a flat vulcanizer, and then at a pressure of 10-12MPa and a temperature of 180-200°C for 2-5 minutes to obtain a modified plastic.
7. The method for preparing a modified plastic according to claim 6, characterized in that: In S1, the material-ball ratio of the ball mill is 1:2, and the rotation speed of the ball mill is 300 r / min.
8. The use of a modified plastic according to any one of claims 1 to 5, characterized in that: The applications include packaging materials, electronic and electrical materials, and automotive industry materials.
Citation Information
Patent Citations
Antibacterial polycarbonate plastic
CN112980173A
Antibacterial anti-aging plastic
CN116875020A